2016
DOI: 10.1016/j.compag.2016.03.020
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility cachaca type recognition using computer vision and pattern recognition

Abstract: a b s t r a c tBrazilian rum (also known as cachaça) is the third most commonly consumed distilled alcoholic drink in the world, with approximately 2.5 billion liters produced each year. It is a traditional drink with refined features and a delicate aroma that is produced mainly in Brazil but consumed in many countries. It can be aged in various types of wood for 1-3 years, which adds aroma and a distinctive flavor with different characteristics that affect the price. A research challenge is to develop a cheap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…14,16,17,19 Although the models developed by Rodrigues co-workers exhibited better qualitative performance parameters, commercial samples were not used for their construction and validation, significantly reducing the data variance, and consequently the applicability and robustness of these models. 17,19 Moreover, one more disadvantage presented by the models developed by Rodrigues et al was the need for several steps of complex image-processing methods. 17 The model developed in this work showed performance parameters similar to the models by Fernandes et al, 14 and better performance parameters than those by Bernardes and Barbeira.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14,16,17,19 Although the models developed by Rodrigues co-workers exhibited better qualitative performance parameters, commercial samples were not used for their construction and validation, significantly reducing the data variance, and consequently the applicability and robustness of these models. 17,19 Moreover, one more disadvantage presented by the models developed by Rodrigues et al was the need for several steps of complex image-processing methods. 17 The model developed in this work showed performance parameters similar to the models by Fernandes et al, 14 and better performance parameters than those by Bernardes and Barbeira.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13] A brief description of works that present the separation of aged cachaças by the wood used in the maturation process using different analytical and chemometric methods is shown in Table 1. [14][15][16][17][18][19][20][21][22][23] The following unsupervised exploratory methods: principal component analysis (PCA) and hierarchical cluster analysis have been used in combination with high-performance liquid chromatography coupled with diode array detection, 15,18,20 sensorial analysis, 21 electrospray ionization mass spectrometry, 22 and electronic spectroscopy. 23 Supervised classification methods have also been used: Rodrigues and co-workers presented models using artificial neural networks, k-nearest neighbor, linear discriminant analysis, quadratic discriminant analysis, multilayer perceptron, and support vector machine coupled to a computer vision system and chemical information, obtaining accuracy up to 100%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pérez-Caballero et al [157], reported classification accuracies of above 94% in differentiating between white, rested, aged, and extra-aged tequilas using RF and SVM. Making use of the ensemble of MLP, SVM and NB, Rodrigues et al [158] were able to classify Brazilian rum by aging time and wood type used during the aging process. By co-averaging the individual classifiers, accuracies of 100% was achieved for the wood type and 85.7% for aging time.…”
Section: Vegetablesmentioning
confidence: 99%
“…The authors compared different algorithms from discriminant analysis, SVM, and counter-propagation ANN, getting the best results from quadratic discriminant analysis combined with principal components analysis (PCA) with an accuracy of 89%. On the other hand, Rodrigues et al [101] assessed the chemical components and color in RGB and CIELab scales of Cachaça samples and used those values as inputs to develop ANN models to classify the beverages according to (i) age and (ii) type of wood used for aging.…”
Section: Machine Learning In Alcoholic Beveragesmentioning
confidence: 99%